ANALISIS KEPUTUSAN PEMBELIAN PRODUK HONDA BEAT DI KOTA BATAM: Brand Image, Product Design, Product quality, Purchase Decision. - Alif, Nauval; Evyanto, Winda (LPPM Universitas Putera Batam, 2024)
Along with the needs and demands of the community for adequate transportation facilities, thus encouraging the development of the automotive industry in Indonesia to accelerate and tend to increase every year. In Batam city itself, motorcycle competition is very tight, because the majority of the population works in various industrial sectors. People value using motorcycles as a means of transportation. Quantitative method as a method by analyzing data on populations or samples for testing predetermined hypotheses. The population contained in this study are all users of the Honda Beat infinite brand motorbikes in the city of Batam. The calculated F value is 75.579 and the significant value obtained is 0.000 below the required value of 0.05 and above the F table value of 2.70, thus simultaneously the variables in this study have an effect on the dependent variable. The variable product quality, product design is below the significant value of 0.05 and higher than the t table of 1.984, meaning that both variables have a significant effect on purchasing decisions. Brand image variable has a value below significant, it is stated that it has no significant effect on purchasing decisions.